2019
DOI: 10.25083/rbl/24.3/395.399
|View full text |Cite
|
Sign up to set email alerts
|

Description of vancomycin resistance genes in Enterococcus sp. clinical strains isolated from Bucharest, Romania

Abstract: Vancomycin Resistant Enterococci (VRE) are a major cause of nosocomial infections. The purpose of this study was the investigation of the genetic background of vancomycin resistance in VRE strains isolated from various clinical sources in a major hospital in Bucharest. Identification of Enterococcus faecium and E. faecalis at the species level was performed using multiplex PCR for species specific ddl (D-alanine-D-alanine ligase) genes, as for 64% of the strains the VITEK system revealed only the genus of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…We found that the prevalence of vancomycin resistant E. faecium strains was higher than that of E. faecalis, which is similar with the results of another study [14] that reported that out of 23 VRE strains isolated from different clinical specimens at the same hospital in Bucharest, Romania, 18 strains were identified as E. faecium and 5 were E. faecalis. 16 E. faecium strains carried the vanA genotype and 2 strains had the vanB genotype.…”
Section: Prevalence Of Vancomycin Resistance Phenotypes Among Enterocsupporting
confidence: 90%
“…We found that the prevalence of vancomycin resistant E. faecium strains was higher than that of E. faecalis, which is similar with the results of another study [14] that reported that out of 23 VRE strains isolated from different clinical specimens at the same hospital in Bucharest, Romania, 18 strains were identified as E. faecium and 5 were E. faecalis. 16 E. faecium strains carried the vanA genotype and 2 strains had the vanB genotype.…”
Section: Prevalence Of Vancomycin Resistance Phenotypes Among Enterocsupporting
confidence: 90%
“…In order to investigate the genetic support of β-lactam enzymatic resistance (carbapenemases, ESBLs), bacterial DNA was extracted using an adapted alkaline extraction method ( Almahdawy et al, 2019 ). The genetic background of AR was investigated by PCR (PCR Master Mix 2X, Thermo Scientific), using 1 μl of DNA and specific primers for bla TEM ( Quinteros et al, 2003 ), bla SHV ( Kim and Lee, 2000 ), bla CTX–M ( Israil et al, 2013 ), bla OXA– 48 ( Poirel et al, 2011 ), bla VIM ( Shirani et al, 2016 ), bla IMP ( Shirani et al, 2016 ), bla NDM ( Nordmann et al, 2011 ), bla SIM ( Qi et al, 2008 ), bla SPM ( Ellington et al, 2007 ), and bla KPC ( Poirel et al, 2011 ) genes ( Supplementary Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies demonstrate that a significant proportion of antibiotic-resistant genes in bacteria can be attributed to genetics. The transfer of genetic material between bacteria, via transformation and transduction, is considered the main factor responsible for antibiotic resistance in the majority of bacterial strains [134][135][136].…”
Section: Discussionmentioning
confidence: 99%